Molecular Analysis of Microdissected Tumors and Preneoplastic Intraductal Lesions in Pancreatic Carcinoma - Heinmöller, Ernst (American Society for Investigative Pathology, 2000)
Little or no data exist concerning the inactivation of tumor suppressor genes in intraductal lesions surrounding invasive ductal pancreatic carcinomas. Using a novel improved primer extension and preamplification polymerase chain reaction, we analyzed microdissected paraffin-embedded specimens of pancreatic carcinoma (n = 29) and their corresponding pancreatic intraductal lesions (PIL, n = 331) for loss of heterozygosity (LOH) of p16(INK4), DPC4, and p53 by microsatellite analysis and for p53 protein by immunohistochemistry. LOH at the p16(INK4) locus (9p21) was found in nine of 22 informative tumors (41%), in 15 of 25 tumors (60%) at the DPC4 locus (18q21.1), and in 22 of 27 tumors (81%) at the p53 locus (17p13). Homozygous deletions of p16(INK4) and DPC4 were found in eight of 22 (36%) and four of 25 tumors (16%), respectively. Furthermore, 24 of 29 tumors (83%) revealed considerable intratumoral genetic heterogeneity. In 165 of 277 PILs (60%) having suitable DNA for microsatellite analysis, alterations in at least one tumor suppressor gene were found. In individual PILs, up to three alterations were detected, and p53 LOH occurred even in morphologically normal-appearing ductal epithelium near the tumor. Although deletions of all three tumor suppressor genes were found in PILs without nuclear atypia, there was a tendency toward earlier LOH of p16(INK4) compared to DPC4 and p53 in these lesions. LOH in tumors accompanied positive p53 immunohistochemistry in 81% but only in 38% in PILs.